Treatment options for recurrent high-grade gliomas. (January 2017) - Birk, Harjus S; Han, Seunggu J; Butowski, Nicholas A
High-grade gliomas are aggressive brain tumors encompassing Grade III and IV classifications. Of these, glioblastoma (GB) is the most malignant with a high rate of recurrence after initial resection. Although standard treatment does exist for newly diagnosed GBs, therapeutic strategies for recurrent GB are less solidified. However, mounting evidence describes the role of re-resection, bevacizumab, chemotherapy, targeted molecular therapies, immunotherapeutic approaches and radiotherapy in recurrent GB management. This review article provides analysis of the aforementioned therapies, through assessing their effect on overall survival. Because GB tumor heterogeneity is prevalent there is a constant need to investigate therapies targeting recurrence. Studies evaluating both therapeutic targets and strategies for high-grade gliomas are and will remain invaluable.